2022
DOI: 10.1002/cphc.202200337
|View full text |Cite
|
Sign up to set email alerts
|

The Inner Hydration in Surfactant/Cholesterol Vesicles Differs from the Outer One: A Spectroscopic Investigation

Abstract: Vesicles contain two aqueous regions: inner core and outer-tobulk. It has remained an open question whether hydration behaviour in the inner core differs from the outer-to-bulk region, mostly owning to the inability of the conventional spectroscopic techniques to deconvolute the contribution from these two regions. We, using THz-FTIR spectroscopy (1.5-13.5 THz) experimentally probe the inner hydration of three differently charged surfactant/cholesterol vesicles composed of SDS, CTAB and Brij 30. Both dynamic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In our previous study, we observed that the addition of cholesterol does not perturb the hydration of the surfactant interface. 23 This leads us to approximate that in the lipid interface also, cholesterol would not affect the interfacial hydration noticeably and we take a hyd % a 0 hyd , which finally concludes that f 0 hyd 4 f hyd . This inequality leads to very useful information as it manifests that more water molecules are accommodated in the hydration layer of lipids in the presence of cholesterol compared to the unmodified liposomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we observed that the addition of cholesterol does not perturb the hydration of the surfactant interface. 23 This leads us to approximate that in the lipid interface also, cholesterol would not affect the interfacial hydration noticeably and we take a hyd % a 0 hyd , which finally concludes that f 0 hyd 4 f hyd . This inequality leads to very useful information as it manifests that more water molecules are accommodated in the hydration layer of lipids in the presence of cholesterol compared to the unmodified liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…THz measurements enables us to explicitly determine the hydration at the interface as the calculation of Δ α ( ν ) subtracts the bulk contribution. 23 Thus, the estimated peak frequencies and lifetimes manifest the interfacial information only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more explicit insight of protein hydration is obtained from the difference spectra, Δα(ν) = α(ν) protein+salt+water – α(ν) salt+water (Figure ). Interestingly, the Δα(ν) profiles are not featureless, rather they show certain peaks, and the overall Δα(ν) profiles could be fitted using a damped harmonic oscillator model ,, normalΔ α ( ν ) = i = 1 N a i ω 0 , i ν 2 4 π 3 true[ ν 2 ω 0 , i 2 π 2 + ( ν d , i 2 + ω 0 , i 2 4 π 2 ν 2 ) 2 true] where a i , ω 0, i , and ν d , i stand for the amplitude, the damping width, and the center frequency of the i th damped harmonic oscillator mode, respectively (see the Supporting Information section for details). Two representative fitting profiles for pure BSA and La 3+ -containing BSA (both incubated at 70 °C) are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, extensive studies on structural properties of aqueous solutions have been conducted using IR and Raman spectroscopy, inelastic neutron diffraction, X-ray diffraction, and terahertz (THz) spectroscopic techniques. The effects of ions on the dynamics of water have been primarily obtained from various time-resolved spectroscopic techniques, such as femtosecond nonlinear IR spectroscopy, dielectric relaxation spectroscopy, and ultrafast optical Kerr effect (OKE) spectroscopy. ,,, The water molecules in ionic hydration shells influence the interactions and dynamics of hydrogen bond network dynamics and such changes can be captured through terahertz (THz) spectroscopy. ,, Far infrared or THz spectroscopy is a unique technique for studying the intermolecular structure and dynamics of ionic solutions, including specific ion effects. , …”
Section: Introductionmentioning
confidence: 99%